2005
DOI: 10.1021/jf048082o
|View full text |Cite
|
Sign up to set email alerts
|

Addition of Glycine Reduces the Content of Acrylamide in Cereal and Potato Products

Abstract: The effects of adding amino acids on the content of acrylamide in potato crisps, French fries, flat breads, and bread crusts were investigated. Addition of glycine or glutamine during blanching of crisps reduced the amount of acrylamide by approximately 30% compared to no addition. No effect was found in French fries. Addition of glycine during doughmaking significantly reduced acrylamide in both flat breads and bread crusts. In bread crusts the reduction of acrylamide ranged from 50 to >90% depending on the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
62
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(73 citation statements)
references
References 21 publications
10
62
0
1
Order By: Relevance
“…L-cysteine appeared to reduce the acrylamide content in the most effective way, with a reduction of about 92%, followed by L-lysine (39%) and glycine (24%). These results confirm previous investigations and above-mentioned hypotheses, although there were some differences in degree of reduction between different studies (Bråthen et al, 2005;Kim et al, 2005;Rydberg et al, 2003). Rydberg et al (2003) for instance found a more efficient acrylamide reduction of glycine compared to L-lysine in a potato model system.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modsupporting
confidence: 91%
See 2 more Smart Citations
“…L-cysteine appeared to reduce the acrylamide content in the most effective way, with a reduction of about 92%, followed by L-lysine (39%) and glycine (24%). These results confirm previous investigations and above-mentioned hypotheses, although there were some differences in degree of reduction between different studies (Bråthen et al, 2005;Kim et al, 2005;Rydberg et al, 2003). Rydberg et al (2003) for instance found a more efficient acrylamide reduction of glycine compared to L-lysine in a potato model system.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modsupporting
confidence: 91%
“…In literature, conflicting results were found for this amino acid. Several studies showed a significant decrease upon addition of free L-glutamine (Bråthen et al, 2005;Hanley et al, 2005;Rydberg et al, 2003). Similar to our results, Claeys et al (2005) observed an increase, although this was not attributed to a direct acrylamide formation from the amino acid.…”
Section: Influence Of Additives On Acrylamide Formation In Potato Modsupporting
confidence: 90%
See 1 more Smart Citation
“…This hypothesis is supported by earlier studies, in which amino acids with nucleophilic side chains considerably decrease levels of the free ACR, due to Michael-type addition reactions producing the corresponding 3-(alkylamino)-propionamide (Adams et al, 2010;Koutsidis et al, 2009;Zamora, Delgado, & Hidalgo, 2010). In addition, it is known that the addition of free amino acids other than the ACR precursor asparagine, such as glycine, lysine and cysteine, can reduce ACR concentrations in thermally treated foods (Brathen, Kita, Knutsen, & Wicklund, 2005;Rydberg et al, 2003). But the exact mechanisms of ACR degradation and adduct-formation in food products remain unknown (Adams et al, 2010).…”
Section: Discussionsupporting
confidence: 60%
“…-El impacto del almacenamiento en los niveles libres de asparragina. -Ensayos de laboratorio donde las rodajas de la patata se han empapado en soluciones del glicina o glutamina (Bråthen et al, 2005). -Desactivación de la asparragina mediante el uso de cationes di-y trivalentes.…”
Section: Asparragina (Escala De Laboratorio Y Producción Piloto)unclassified